Tinnitus emerging in the context of a COVID-19 infection seems not to differ in its characteristics from tinnitus unrelated to COVID-19 - Figueiredo, Ricardo R.; Penido, Norma de O.; Azevedo, Andréia A. de; Oliveira, Patrícia M. de; Siqueira, Adriana G. de; Figueiredo, Guilherme de M. R.; Schlee, Winfried; Langguth, Berthold (Frontiers in Neurology, 2022)
Background and Aim: COVID-19 is a respiratory disease caused by the new coronavirus SARS-CoV-2, for which the first cases were reported in China, by December 2019. Viral infections may cause hearing loss and, tinnitus. Our aim is to explore the relationship between COVID-19 and tinnitus. For this purpose we analyzed a sample of people who had suffered from a COVID infection in the city of Volta Redonda, Brazil. In detail, we compared those with new onset tinnitus during or after the COVID infection with those without tinnitus and those with tinnitus onset before the COVID infection. Methods: Fifty-seven patients over 18 years old and previously diagnosed with COVID-19 were included. Patients were subdivided in three groups: no tinnitus (NT), chronic tinnitus, CT) and tinnitus that arose during or after COVID (post-COVID tinnitus, PCT). Medical history, tonal audiometry, otoacoustic emissions were performed, and tinnitus patients fulfilled the Tinnitus Handicap Inventory (THI) and visual-analog scales (VAS) for loudness and distress. Results: PCT was reported by 19.3% of the patients, while 22.8% reported CT. No statistical difference was found between CT and PCT concerning hearing function, tinnitus characteristics and tinnitus distress. There was also no statistically significant difference between PCT and NT with respect to COVID symptoms and pharmacological COVID treatment, and 30.8% of the patients with CT reported worsening of their tinnitus after COVID. Conclusion: As with other viral infections, inner ear symptoms, including tinnitus, may be associated with COVID. In our sample patients with tinnitus onset before COVID and those with tinnitus onset during or after COVID did not differ significantly in their clinical characteristics and their hearing function, suggesting that tinnitus occurring in the context of a COVID infection is not related to a unique pathophysiological mechanism. Although some drugs used to treat tinnitus are known to damage the inner ear cells (especially hydroxychloroquine), we did not see any relationship between the intake of these drugs and tinnitus onset, eventually due to the short prescription time and low doses. For further exploring the relationship of tinnitus and COVID, large population based studies are warranted.